AB1376 Urinary monocyte chemoattractant protein 1 cannot differentiate between histological classes of lupus nephritis. (12th June 2018) - Gone, R.K.; Dhir, V.; Sandhu, A.; Sharma, A.; Rathi, M.; Nada, R.; Sharma, S.; Sharma, S.K.
Abstract : Background: Lupus Nephritis, one of the commonest manifestation of SLE, seen in 60% of adult SLE patients at some point of time, carries poor prognosis when compared to those with no renal involvement. The natural course of the LN has recurrent flares, necessitating the need for early detection and treatment. Despite being the gold standard in diagnosing Lupus nephritis and its severity, renal biopsy is an invasive procedure with potential complications, and difficult to repeat. Hence, a novel biomarker, reflecting the disease activity and severity is needed to predict flare. Monocyte chemoattractant Protein 1, a chemokine produced locally during Lupus Nephritis flare, was shown in many previous studies as a promising biomarker Objectives: We studied the role of Urinary MCP-1 as a biomarker of disease activity in LN and compare its value among different histological classes of Lupus nephritis Methods: This is a case-control study conducted at a tertiary care centre in North India from July 2016 to December 2017. Cases were those patients undergoing renal biopsy satisfying the inclusion criteria set for SLE with LN(n=36). Controls were patients of SLE without active LN [Control I-prior LN (n=11) and Control II-never had LN (n=15)]. Urinary MCP-1 measurement was done using Sandwich ELISA kit Results: The mean age in cases was 31.1±10.2 years and mean age in control-I was 34.6±8.0 and in control II was 36.3±10.4. Urinary MCP-1 values in cases (1214±1467.1 pg/mg) was significantly higher compared to Controls (184.5±186.8). However, no significant difference was observed between Control I (170.5±150.8) and Control II (194±214). Urinary MCP-1 levels show significant correlation when compared with classical disease markers like 24 hour proteinuria, 24 hour PCR, Spot PCR and SLEDAI. Cut off value (339 pg/mg, p<0.001) obtained from ROC curve has sensitivity and specificity of 80% and 92% respectively. However, there was no significant difference of Urinary MCP-1 levels was observed among different classes of LN (p=0.593). ROC curve comparison of urinary MCP-1 (AUC=0.879) with 24 hour urine protein to creatinine ratio (AUC=0.964) and spot urine protein to creatinine ratio (AUC=0.872) showed that it is not a better marker of disease activity than both of them. Urinary MCP-1 levels didn't show significant correlation with Renal activity index calculated on renal biopsy. Conclusions: In this study we found higher Urinary MCP-1 levels in active LN compared to Inactive LN and its level was correlated well with the presently used disease markers. However there was no significant difference among different histological classes of LN. Disclosure of Interest: None declared